Entrenamiento de la fureza explositiva para mejorar el rendimiento deportivo de los velocistas de 100 mts de la categoria juvenil "a" de la Federación Deportiva de Chimborazo en el periodo de diciembre de 2010- abril 2011 - Latorre, José (2012)
Explosive strength training to improve athletic performance of 100 meters sprinters of the youth category "a" of Sports Federation of Chimborazo from December 2010 to April 2011 period. Objective: To characterize the explosive strength training for sprinters 100 meters from the youth category "A" of Sports Federation of Chimborazo from December 2010 to April 2011 period.